Time to CT head in adult patients with suspected traumatic brain injury: Association with the 'Shorter Stays in Emergency Departments' health target in Aotearoa New Zealand. Issue 9 (September 2018) - Jones, Peter; Athaullah, Waheedah; Harper, Alana; Wells, Susan; LeFevre, James; Stewart, Joanna; Curtis, Elana; Reid, Papaarangi; Ameratunga, Shanthi
Abstract: A national health target for length of stay in emergency departments (ED) was introduced in 2009 to reduce crowding and improve quality of care. We aimed to determine whether the target was associated with changes in time to CT and appropriateness of CT imaging, as markers of care quality for suspected acute traumatic brain injury (TBI). We undertook a retrospective review of the case records of a random sample of people aged ≥15 years presenting to the ED with TBI from 2006 to 2013. General linear models were used to investigate changes in outcomes along with routine process times before and after the introduction of the target. Among 501 eligible cases the median (IQR) time to CT was 136 (76–247) pre target versus 119 (59–209) minutes post target, p = 0.014. The proportion of appropriate imaging was similar between periods: 77.9% (95% CI 71–83%) versus 76.6% (95%CI 72–81%), p = 0.825. Interactions suggested that the time to CT and appropriateness of imaging before and after the introduction of the target varied by ethnicity, although the changes were not clinically important. Time to assessment and length of stay did not change importantly. We found no evidence of a clinically important change in time to CT or appropriateness of imaging for suspected TBI in association with the introduction of the SSED time target. Additional research with larger cohorts of Māori and Pacific participants is recommended to understand our observed patterns by ethnicity.